Chronic Liver Diseases And Humoral Factors Of Immunity - Sh.Ya.Zakirkhojaev; M.Kh.Talibdzhanova (Genius Publishing Group, 2024)
Scientific research data on Covid-19 shows that 14-53% of patients have signs of mild-tomoderate liver damage: increased levels of aminotransferases, hypoproteinemia, increased prothrombin time. Severity of Covid-19 cases are correlated with extensity of liver damage. On the other hand, prior to infection, active liver disease increased the severity of the infection. SARS-Cov-2 has a feature of direct damage of the hepatocytes which is explained by presence of angiotensin converting enzyme 2 receptors in the cholangiocytes. Patients with chronic diffuse and advanced liver diseases are at higher risk of infection due to cirrhosis affect on immune mechanisms.
Keywords: chronic hepatitis; Covid-19; damage